STRATEGI PEMBIASAAN, KETELADANAN DAN PENGUATAN POSITIF DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) - Nadiyah, Afifatun; Nabilatus Istiqomah; Nurul Faizah Al Muharromah; Moh. Faizin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning Islamic Religious Education (PAI) is not only about understanding the material but also about shaping students' character. However, in practice, PAI learning still prioritizes cognitive aspects. Therefore, strategies are needed to ensure these values ​​are truly applied in everyday life. This article aims to analyze how to implement habituation, role modeling, and positive reinforcement in the PAI learning process. The method used is a literature review with a qualitative descriptive approach. The results indicate that habituation is carried out through regular daily activities, role modeling demonstrated by teachers' attitudes and actions, and positive reinforcement provided by appreciating students' good deeds. These three strategies have proven to complement each other in shaping students' religious character.